The family rule: a framework for obtaining ethical consent for medical interventions from children. - Foreman, D M (1999)
Children's consent to treatment remains a contentious topic, with confusing legal precepts and advice. This paper proposes that informed consent in children should be regarded as shared between children and their families, the balance being determined by implicit, developmentally based negotiations between child and parent--a "family rule" for consent. Consistent, operationalized procedures for ethically obtaining consent can be derived from its application to both routine and contentious situations. Therefore, use of the "family Rule" concept can consistently define negligent procedure in obtaining consent from children, and could be used as a unifying framework in the development of new professional guidelines. A "guideline"-based approach to children's consent to treatment may offer greater individuality than a "rights"-based approach, though careful training and oversight will be needed for it to be effective.